How Digitalization and Service Excellence Drive Sharia Bank Customer Satisfaction? - Rahmawati, Sinta Dewi; Triwoelandari, Retno; Kartika, Tika (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2025)
In the current digital era, banking is experiencing a major transformation by using digital technology to improve efficiency and banking services. Bank digitalization includes various innovations such as mobile banking, internet banking, and the use of AI technology in providing customer service. Apart from that, service quality and product quality are also important factors that influence customer satisfaction. This research aims to analyze the influence of bank digitalization, service quality and product quality on customer satisfaction at Bank Syariah Indonesia in Bogor Regency. The method used is a quantitative method with a survey approach. Data was collected through a questionnaire with a sample of 97 respondents using a purposive sampling technique. Data analysis was carried out using multiple linear regression to test the influence of the independent variables, namely bank digitalization, service quality and product quality on the dependent variable, namely customer satisfaction. The research results show that bank digitalization has a positive and significant influence on customer satisfaction. Likewise, service quality and product quality have also been proven to have a positive and significant influence on customer satisfaction, which indicates that banks need to continue to innovate in increasing the digitalization of banking, as well as providing good service and providing quality products so as to increase customer satisfaction. Simultaneously, the three independent variables have a positive and significant influence on customer satisfaction. Another finding in this research is that customer satisfaction is influenced by 91.6% by the variables of bank digitalization, service quality and product quality.